Unravelling the complexities of end-of-life critical care interventions: what drives medico-legal complaints to physicians? - Blier, Marc-André; Aslanova, Rana; Lemay, Karen; Jin, Shan; Levesque, Teena; Garber, Gary E. (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background This study sought to describe the key medico-legal issues associated with end-of-life critical care interventions in Canada. We explored the most common themes of a disagreement between patients or substitute decision makers (SDM) and treating physicians related to intervention decisions, and complaints against physicians, that were identified and criticised by peer experts as contributing to medico-legal risk. Methods A national repository was retrospectively searched for cases involving end-of-life care that were supported by the Canadian Medical Protective Association (CMPA) between 2018 and 2022. The study involved patients admitted to surgical and medical intensive and critical care units, emergency departments and residents in long term care settings. The frequencies and proportions of the top risk factors leading to medico-legal risks and the most frequent allegations were calculated by exploring factors that contributed to each incident. Results We identified 93 eligible cases, involving 142 physicians. Family medicine was the most frequent specialty named in 32% of the cases. The median age of 93 unique patients was 78 years. Common reasons for complaints were communication breakdown between a physician and a patient/SDM and deficient assessment. The most frequent contributing factors criticised by peer experts were communication breakdown between a physician and a patient/SDM and inadequate documentation. Conclusions The most common omission identified by peer experts involved a physician’s communication with a patient/SDM. Physicians may reduce their medico-legal risk by exploring effective techniques for optimal communication to improve understanding in end-of-life discussions, with the goal of high-quality patient care.